Ontogenic variation of ß-glucuronidase in the liver and intestine of Labeo rohita - Chilke, Arun M (Recent Research in Science and Technology, 2012)
β-Glucuronidase is a lysosomal enzyme, it is largely studied studied in mammalian species. In the present study the attempt was made to localize this enzyme in the liver and intestine during the development of teleost, Labeo rohita. For the demonstration of enzyme activity, Naphthol AS-BI-β-Glucuronide was used as a substrate along with diazotized pararosaniline. β-Glucuronidase shows variation in both the liver and intestine during the development of L. rohita. The enzyme activities in both the organs were increased gradually from 10 to 50 mm stage of development. In the sac-fry (5-7.5mm), the enzyme activity was confined in yolk sac and no enzyme activity was observed in the liver and intestine. It was concluded that the presence of β-glucuronidase in the yolk sac might be due to its role in the yolk metabolism. Gradual increase in enzyme activity from 10mm onwards in the intestine could be due to maturation of digestive tract and in the liver due to increase in the metabolic load with increase in growth and age.